LEXICO-SEMANTIC FEATURES OF LEGAL TERMINOLOGY (Journal of Science-Innovative Research in Uzbekistan, 2025)
The study of legal terminology is an essential aspect of legal translation, given the pivotal role that precise language plays in the interpretation and application of laws. Legal terminology, often complex and highly specific, presents unique challenges when translated across languages. This paper explores the lexico-semantic features of legal terminology in Uzbek and English, highlighting the semantic nuances, contextual usage, and translation challenges. The research provides insights into the impact of language-specific features on the accuracy and effectiveness of legal translation, emphasizing the importance of understanding both linguistic and legal systems in cross-linguistic legal communication.